The relationship between the servant leadership and employee performance at Syarikat Pengurusan Air Pahang Berhad Daerah Jerantut Pahang / Maizatul Natasya Ajerah Nazri - Nazri, Maizatul Natasya Ajerah (Faculty of Business and Management, 2019)
This study was conducted to analyze the relationship between the servant leadership and the employee performance at Syarikat Pengurusan Air Pahang Berhad Daerah Jerantut, Pahang. The 56 sample of staff from the company was used in this study. Data were collected through the questionnaires which were distributed personally to the respondents. Data were analyzed by using SPSS and the findings showed that majority of the respondents believed that the elements or components of servant leadership were influenced the level of the employee performance in the organization. They know that the good of leadership may lead the good employee performance too. The result of the study can be used to improve the leadership style to assign the future requirements for employee performance.